Attainment of Targets of the 20-Year Infancy-Onset Dietary Intervention and Blood Pressure Across Childhood and Young Adulthood: The Special Turku Coronary Risk Factor Intervention Project (STRIP). Issue 5 (November 2020) - Laitinen, Tomi T.; Nuotio, Joel; Niinikoski, Harri; Juonala, Markus; Rovio, Suvi P.; Viikari, Jorma S.A.; Rönnemaa, Tapani; Magnussen, Costan G.; Sabin, Matthew; Burgner, David; Jokinen, Eero; Lagström, Hanna; et al.
Abstract : We examined whether success in achieving the key targets of an infancy-onset 20-year dietary intervention was associated with blood pressure (BP) from infancy to young adulthood. In the prospective randomized STRIP (Special Turku Coronary Risk Factor Intervention Project; n=877 children), dietary counseling was provided biannually based on the Nordic Nutrition Recommendations primarily to improve the quality of dietary fat in children's diets and secondarily to promote intake of vegetables, fruits, and whole grains. Dietary data and BP were accrued annually from the age of 13 months to 20 years. The dietary targets for fat quality were defined as the ratio of saturated fatty acids to monounsaturated and polyunsaturated fatty acids <1:2 and intake of saturated fatty acids <10 E%, dietary fiber intake in the top age-specific quintile, and dietary sucrose intake as being in the lowest age-specific quintile. Attaining a higher number of the dietary targets was associated with lower systolic BP (mean [SE] systolic BP, 107.3 [0.3], 107.6 [0.3], 106.8 [0.3], and 106.7 [0.5] mm Hg in participants meeting 0, 1, 2, and 3 to 4 targets, respectively; P =0.03) and diastolic BP (mean [SE] diastolic BP, 60.4 [0.2], 60.5 [0.2], 59.9 [0.2], and 59.9 [0.3] mm Hg; P =0.02). When the lowest age-specific quintile of dietary cholesterol was added as an additional target, the association with systolic BP remained significant ( P =0.047), but the association with diastolic BP attenuated ( P =0.13). Achieving the key targets of an infancy-onset 20-year dietary intervention, reflecting dietary guidelines, was favorably albeit modestly associated with systolic and diastolic BP from infancy to young adulthood. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00223600. Abstract : Supplemental Digital Content is available in the text.